Indeks Kuning Telur dan Nilai Haugh Unit Telur Puyuh (Coturnix coturnix japonica L.) Hasil Pemeliharaan dengan Penambahan Cahaya Monokromatik - Lestari, Wulan Tri; Tana, Silvana; Isdadiyanto, sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
The aims of this study was to analyze the quality of quail eggs after treatment with the addition of monochromatic red, green and blue light reviewed from the yolk index and Haugh unit values. Treatment started from 4 to 12 weeks. This study used 5 Watts voltage as light resources in the night during 12 hours / day. Parameters in this study were index of egg yolk (IKT), the Haugh Unit value (HU), feed intake, drink intake, and the weight of the egg. The data of this study was analyzed by Analysis of variance (ANOVA), and if significantly differences continued with Duncan test at 5% significance level. The data researched with blue light treatment showed the IKT and HU was highest value, but the lowest showed on the red light. The highest feed intake on control, but the drink intake didn’t show significant differences. The highest weight of egg showed on the red light treatment. The conclusions of this study was the addition of monochromatic blue light was increased IKT and HU value, therefor had potent to enhance the quality of eggs. Keywords: quail (Coturnix coturnix japonica L.), monochromatic light, egg productivity, IKT, HU